Erlotinib Hydrochloride Novel Drug Delivery Systems: A Mini Review Unravelling the Role of Micro- and Nanocarriers - Taiwade, Chaitali; Fulfager, Aditi; Bhargave, Hardik; Soni, Govind; Yadav, Khushwant (Drug Delivery Letters, 2021)
Erlotinib is a tyrosine kinase inhibitor and it can treat tumors, such as pancreatic and locally advanced lung cancer or metastatic cancer. The traditional formulation of erlotinib currently available is an oral delivery type that presents serious side effects such as hepatotoxicity, skin rashes, gastrointestinal disturbance, renal dysfunction, drug resistance and hematological symptoms. Besides this, other disadvantages of erlotinib provided mostly by oral administration are the comprehensive metabolism, low bioavailability, poor solubility and off-target impact. Overcoming such unfavorable attributes of the medication, innovative medication delivery mechanisms like nanocapsules, liposomes, microspheres, microparticles solid lipid nanoparticles, nanosponge, and nanoparticles have been studied that have really shown their lead over traditional formulations. This article summarizes the novel erlotinib drug delivery systems to boost its clinical efficacy and reduce systemic toxicity. Novel formulations of erlotinib will offer positive outcomes in cancer therapy and will play an important part in improving the drug's therapeutic potential.
Keywords: adverse effects